1993
DOI: 10.1111/j.1600-0773.1993.tb01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glucagon‐Stimulated Glycogenolysis by S‐Nitroso‐N‐acetylpenicillamine*

Abstract: Rat liver is known to contain both a nitric oxide-stimulated guanylate cyclase and a cGMP-stimulated cAMP-phosphodiesterase. To evaluate the possible function of this system, the effect of the nitric oxide generating compound S-nitroso-N-acetylpenicillamine on glycogenolysis was evaluated in isolated rat hepatocytes. S-nitroso-N-acetylpenicillamine (1.0 mM) inhibited glucagon-stimulated glycogenolysis by 15%, but had no effect on basal rates of glycogenolysis. Inhibition of hepatocyte glycogenolysis by S-nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…This observation agrees with the findings that the inhibition of NOS by L-NAME in cultured hepatocytes increases the intracellular levels of glycogen (Donato et al 2001), and that NO donors such as S-nitroso-N-acetylpenicillamine (SNAP) inhibit the biosynthesis of glycogen (Sprangers et al 1998) and may cause discreet inhibition of glycogenolysis stimulated by glucagon (Brass and Vetter 1993). In contrast, Hropot et al (2003) have observed that treatment of rats with L-NAME (25 mg/rat per day for 6 weeks) decreases the content of glycogen, ATP, and creatine phosphate in cardiac tissue, and Kitano et al (2002) have reported that NO has little effect on glycogen synthesis by hepatocytes.…”
Section: Discussionsupporting
confidence: 88%
“…This observation agrees with the findings that the inhibition of NOS by L-NAME in cultured hepatocytes increases the intracellular levels of glycogen (Donato et al 2001), and that NO donors such as S-nitroso-N-acetylpenicillamine (SNAP) inhibit the biosynthesis of glycogen (Sprangers et al 1998) and may cause discreet inhibition of glycogenolysis stimulated by glucagon (Brass and Vetter 1993). In contrast, Hropot et al (2003) have observed that treatment of rats with L-NAME (25 mg/rat per day for 6 weeks) decreases the content of glycogen, ATP, and creatine phosphate in cardiac tissue, and Kitano et al (2002) have reported that NO has little effect on glycogen synthesis by hepatocytes.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, L-canavanine may also have improved energy production by its favorable effects on the endotoxininduced hypoglycemia. Recent studies have reported that this hypoglycemia is largely mediated by NO overproduction, both through a decrease in glucose production, related to inhibition of neoglucogenesis (38,39) and glycogenolysis (40), and an increase in glucose utilization by stimulated macrophages (41).…”
Section: Effects Of L-canavaninementioning
confidence: 99%
“…Our original experimental protocol was modified from the steady state determination of receptor concentrations via Western blot (11) to the measurement of biosynthesis rate by pulse labeling with [ 35 S]Met/Cys. This change in protocol allowed the reduction of 8-Br-cGMP and atrial natriuretic factor (ANF) concentrations used in the present experiments to the level previously employed by others in short term protocols in cultured or isolated hepatocytes (25)(26)(27)(28)(29). HuH-7 cells were grown to near-confluence in MEM supplemented with either 10% FBS or 10% dFBS to which 10 to 1000 M 8-Br-cGMP, 10 nM ANF, or 100 M sodium nitroprusside (SNP) (shown to produce nitric oxide (25), an activator of soluble guanylate cyclase (29)) were added (Fig.…”
Section: Short Term Cgmp-regulated Expression Of Asgr-basedmentioning
confidence: 99%
“…1A). Within 1 h of the addition of 500 M 8-Br-cGMP and activators of both the particulate (ANF) and soluble (SNP) guanylate cyclases (25)(26)(27)(28)(29), the biosynthetic rate of ASGR was increased by 6. tained in MEM supplemented with FBS or dFBS with or without 8-Br-cGMP or its inducers (Fig. 1B).…”
Section: Short Term Cgmp-regulated Expression Of Asgr-basedmentioning
confidence: 99%